Wali Nikah dan Persetujuan Perempuan: Antara Tuntutan dan Kenyataan - Nasution, Khoiruddin (Musawa Jurnal Studi Gender dan Islam, 2007)
Although it is revealed in a patrilinealArab community, Islam is substantially introducinga model of bilateral community which perceives men and woman in an egalitarian position. The purpose of Islam to build an egalitarian, bilateral is explicitly stated in a number of Qur'anic verses and prophetic traditions (hadits). With regard to the issue of wali in a marriage contract, there are Qur'anic verses and hadits which indicate that adult, intelligent women might marry off themselves without a male wali. This view is in conformity with that applauded by the Hanafis who argue that adult women, just like adult men, might marry off themselves. Such interpretation, in the opinion of the writer, is the one to serve the purpose of Islam in developing an egalitarian community.